Reducing violence against children by implementing the preventative intervention Interaction Competencies with Children for Teachers (ICC-T) - Ssenyonga, Joseph; Hermenau, Katharin; Nkuba, Mabula; Hecker, Tobias (Department of Psychology, Bielefeld University, 2018)
An adolescent's school is often the second most important place for his development and education after the home. However, reports highlight the recurrence of the use of violent discipline in schools. There are few school-based interventions that aim at reducing violence at school that have been implemented and evaluated in sub-Saharan Africa. To reduce violent disciplinary measures used at school, we aim to implement and evaluate the feasibility and efficacy of the preventative intervention Interaction Competencies with Children for Teachers (ICC-T).
study protocol for a cluster randomized controlled trial in Southwestern Uganda
Keywords: School violence; Students; Behavioral problems; Secondary school; Teachers